Band gap prediction of the alloying halide perovskites using GW compare to DFT-1/2 method - K. Amnuyswat; P. Thanomngam (My University, 2020)
The outstanding optoelectronic properties of methylammonium halide perovskites, including the tunable spectral absorption range, high carrier mobilities and low carrier recombination rates, make these materials are interesting for a decade year. In my works, a first-principle calculation based on non-local van der Waals-corrected Density Functional Theory (vdW-DFT) is performed to investigate high accuracy atomic structures and their properties of the alloying halide perovskites (CH3NH3PbIxBr1-x). While DFT generally underestimates the band gap for practically semiconductors and insulators, it provided a surprising accurate value for methylammonium halide perovskites. Unfortunately, this performance is not existing to another hybrid halide perovskite. The relativistic GW approximation is known to be a better-provided band gap more accurately, but at an extremely high computational cost were applied to the study. Here we also report the efficiency and accuracy of the bandgap calculations of methylammonium halide perovskites by using the self-consistent quasiparticle GW method (scGW) incorporated with the spin-orbit coupling comparing to recent develops DFT-1/2 method. The latter computational scheme provides accurate band gaps with the precision of the scGW method with no more computational cost than standard DFT. This method can solve the band gap problem by correcting the half-hole/half-electron occupation in the pseudopotentials. This work yields the possibility of the band gap prediction of alloying halide perovskite material (CH3NH3PbIxBr1-x) that good for optoelectronic design such as planar dye solar cell.
Keywords: Perovskite Materials and Applications